FACTORS AFFECTING JOB SATISFACTION OF EMPLOYEES IN INDUSTRY TECHNOLOGY HIGH SCHOOL YOGYAKARTA - SUHARTO, SUHARTO (Management, 2010)
In an era of progress in science and technology today many people`s sense of being replaced by sophisticated machines. So that needs less and less human labor. But the machines that use advanced technology can not operate without a human role as an operator in the field. To operate a machine needs to be required qualified manpower in the field technology. Company objectives to be achieved can not be separated from the role of employees. In this case the employee is expected not as objects in achieving corporate objectives, but also noted as a principal or employee participation in achieving objectives. For that in the process of employee recruitment selection process needs to be done in accordance with applicable procedures. So expect to obtain prospective employees who have the skills and basic skills needed company. These skills is a product of the educational system and organizational other experience.From obtained from simple regression analysis and multiple linear regression analysis was obtained this information, the salary received by employees SMTI Yogyakarta has a significant and positive impact on job satisfaction. This means that the higher the salary, the more the level of job satisfaction. Benefits received by employees SMTI Yogyakarta has a significant and positive impact on job satisfaction. This means the higher the allowance, the level of employee job satisfaction is also higher. Isentif received by employees SMTI Yogyakarta has a significant and positive impact on job satisfaction. This means the higher the Isentif then the level of job satisfaction also. Relationships Between Employees at SMTI Yogyakarta has a significant and positive impact on job satisfaction. This means the better the relationship between employees, the higher employee job satisfaction. SMTI employee facility in Yogyakarta has a significant and positive impact on satisfaction. This means better facilities, either physical or psychological work will impact the increased employee job satisfaction. Together turns Salaries, Allowances, Isentif, Relationships Between Employees, Working facilities have a significant influence on the level of employee job satisfaction. From the results of multiple regression analysis showed that the level of employee job satisfaction, 70.3% the cause is of these variables, while the remainder are caused by lain.